2009
DOI: 10.1007/s11270-009-0292-5
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Fatty Acids from Palm Oil Effluent by Combined Electro-Fenton and Biological Oxidation Process

Abstract: The main objective of this study was to find out a cost-effective treatment methodology for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Parilti in 2010 21 investigated 38 % enhancement in BOD5/COD ratio by adopting solar oxidation by hydrogen peroxide process. Babu et al 22 reported 35 % and 48 % depletion in BOD5 and COD respectively by electro-fenton process resulting in 16 % rise in BOD5/COD ratio. According to our treatment strategy, oxidation by hydrogen peroxide time and dose were kept low intentionally to facilitate subsequent biological degradation in a view to achieve a plenty of enhancement in BOD5/COD ratio and tiny depletion in TCOD.…”
Section: Resultsmentioning
confidence: 99%
“…Parilti in 2010 21 investigated 38 % enhancement in BOD5/COD ratio by adopting solar oxidation by hydrogen peroxide process. Babu et al 22 reported 35 % and 48 % depletion in BOD5 and COD respectively by electro-fenton process resulting in 16 % rise in BOD5/COD ratio. According to our treatment strategy, oxidation by hydrogen peroxide time and dose were kept low intentionally to facilitate subsequent biological degradation in a view to achieve a plenty of enhancement in BOD5/COD ratio and tiny depletion in TCOD.…”
Section: Resultsmentioning
confidence: 99%
“…serves as a source for hydroxyl radicals, as reported by Babu et al (2010). Hence, the doping of Fe on SnO 2 /Ti anode may increase radical concentration to a great extent, leading to the efficient degradation of organic pollutants.…”
Section: Electro-oxidation Mechanismmentioning
confidence: 86%
“…produces hydroxyl radical, which has a strong affinity for organic bond rupture (Babu et al 2010). Hence, Fe can be considered as a better dopant.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in EFOPs, cathodic reactions generate the Fenton reagent: the cathode not only reduces Fe 3+ to Fe 2+ but also generates H 2 O 2 by reducing O 2 . For the reduction of Fe 3+ , stainless steel and graphite are frequently used as cathode materials. Generally, carbonaceous electrodes are employed for the reduction of O 2 to H 2 O 2 ; the gas diffusion electrode (GDE) configuration has recently been adopted for further enhancing the H 2 O 2 production efficiencies. , Additionally, several cathode materials reportedly activate oxidants such as S 2 O 8 2– , HOCl, and H 2 O 2 . Shin et al tested Al, SS, Cu, Sn, and Ti for cathodic conversion of S 2 O 8 2– into SO 4 •– , where Ti exhibited the best performance .…”
Section: Basics Of Eopsmentioning
confidence: 99%